2019
DOI: 10.3390/pathogens8030118
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Multidrug Resistance Patterns of Escherichia coli Isolated from Cloacal Swabs of Live Broiler Chickens in Bangladesh

Abstract: Antimicrobial resistance is a major health problem, particularly in developing countries like Bangladesh, where there is a paucity of information on resistance patterns and prevalence of antimicrobial determinants. Therefore, the aims of this study were to investigate the prevalence of resistance, including multi-drug resistance (MDR), and the associated genetic determinants in Escherichia coli isolates from cloacal swabs of live broiler chickens in Bangladesh. Altogether, 400 cloacal swabs (200 from Rajshahi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
43
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 34 publications
12
43
3
1
Order By: Relevance
“…This is in agreement with Hadiujjaman et al [ 42 ] and Islam et al [ 43 ], who reported the E. coli prevalence in layers to be 80% and 85% in Bangladesh. Al Azad et al [ 44 ] reported an isolation rate of E. coli of 100% in poultry, which is rather higher than ours. However, the observed variation in the prevalence of E. coli in poultry farms may be linked with differences in isolation methods, geographic locations, hygienic practices, sanitation, and other management practices in farms.…”
Section: Discussioncontrasting
confidence: 73%
“…This is in agreement with Hadiujjaman et al [ 42 ] and Islam et al [ 43 ], who reported the E. coli prevalence in layers to be 80% and 85% in Bangladesh. Al Azad et al [ 44 ] reported an isolation rate of E. coli of 100% in poultry, which is rather higher than ours. However, the observed variation in the prevalence of E. coli in poultry farms may be linked with differences in isolation methods, geographic locations, hygienic practices, sanitation, and other management practices in farms.…”
Section: Discussioncontrasting
confidence: 73%
“…The isolation of Salmonella from poultry was previously reported in Bangladesh, however, none of these studies focused on the molecular detection of resistance genes [23][24][25][26]. However, resistance genes were detected in Escherichia coli isolated from cloacal swabs of boiler chicks in Bangladesh [27,28]. Moreover, a study in Bangladesh, detected resistance genes in E. coli and Salmonella from dairy farms [29].…”
Section: Introductionmentioning
confidence: 99%
“…The CTX-M type ESBL-producing E. coli is the most dominant globally [ 19 ]. In Bangladesh, bla CTX-M-1 (94.4%) and bla TEM (50–91.3%) ESBL-producing E. coli were reported in droppings of chickens [ 20 , 21 , 22 ]. Chickens are considered as a potential reservoir of ESBL-producing E. coli [ 23 ].…”
Section: Introductionmentioning
confidence: 99%